Communication, cognitive functioning, and feeding and swallowing information needs of caregivers of individuals diagnosed with alzheimer’s disease within a support group setting - Le Roux, Carla (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSL&HT)--Stellenbosch University, 2022.